Tiga dekade laju perubahan garis pantai di Kota Dumai - Aras Mulyadi; Rasoel Hamidy; Musrifin Musrifin; Efriyeldi Efriyeldi; Romie Jhonnerie (Dinamika Lingkungan Indonesia, 2022)
Mapping of coastline changes helps in coastal development and monitoring. The city of Dumai, on the east coast of Riau Province, has undergone significant and radical changes caused by the intervention of humans and nature over the past three decades. This study mapped and measured the rate of change of the coastline of Dumai City for 30 years. The Landsat (TM, and OLI) image series, 1990, 1999, 2008, and 2020 became a data source to generate coastlines through on-screen digitization techniques, then to study the temporal behavior of coastlines using the Digital Shoreline Analysis System (DSAS) and geographic information systems to describe the spatial and temporal variations of coastlines. The results showed that the coastline length during the observation ranged from 123,14 to 125,23 km, while the average accretion rate was 1.17 meters per year while the average abrasion rate was 2.04 meters per year. Those rates of change affected coastline expanded to the sea for 60,82 hectares and eroded 760,20 hectares coastline to the land.